LENGTH AND LETTER COMBINATION. VOCABULARY OF FIRST DECLENSION NOUNS (International conference on multidisciplinary science, 2023)
In this article it is explained about the Latin 1st declension nouns that considered as group of nouns that follow a specific pattern of inflection. The authors analyze nouns that are typically feminine and  nominative singular form. Nouns are declined to indicate their grammatical function in a sentence, such as whether they are the subject, object, or possessive.